1993
DOI: 10.1128/jb.175.11.3253-3258.1993
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of urea by Ureaplasma urealyticum generates a transmembrane potential with resultant ATP synthesis

Abstract: When urea is added to Ureaplasma urealyticum, it is hydrolysed internally by a cytosolic urease. Under our measuring conditions, and at an external pH of 6.0, urea hydrolysis caused an ammonia chemical potential equivalent to almost 80 mV and, simultaneously, an increase in proton electrochemical potential (h) of about 24 mV with resultant de novo ATP synthesis. Inhibition of the urease with the potent inhibitor flurofamide abolished both the chemical potential and the increase of Ap such that ATP synthesis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
67
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 22 publications
3
67
0
3
Order By: Relevance
“…The dependence of ureaplasmas on urea for growth has led to the hypothesis that intracellular urea hydrolysis and the resulting intracellular accumulation of ammonia/ammonium ions is coupled to ATP synthesis through a chemiosmotic type of mechanism (356). Experimental support for the generation of a transmembrane potential, with resultant ATP synthesis through the ureaplasmal F O F 1 -type ATPase, first provided by Romano et al (383) was more recently extended and confirmed by Smith et al (428). At an external pH of 6.0, the pH optimum for ureaplasma growth in vitro, urea hydrolysis generated an ammonia chemical potential equivalent to almost 80 mV and, simultaneously, an increase in proton electrochemical potential (⌬p) of about 24 mV with resultant de novo synthesis of ATP (428).…”
Section: Energy-yielding Pathwaysmentioning
confidence: 85%
See 4 more Smart Citations
“…The dependence of ureaplasmas on urea for growth has led to the hypothesis that intracellular urea hydrolysis and the resulting intracellular accumulation of ammonia/ammonium ions is coupled to ATP synthesis through a chemiosmotic type of mechanism (356). Experimental support for the generation of a transmembrane potential, with resultant ATP synthesis through the ureaplasmal F O F 1 -type ATPase, first provided by Romano et al (383) was more recently extended and confirmed by Smith et al (428). At an external pH of 6.0, the pH optimum for ureaplasma growth in vitro, urea hydrolysis generated an ammonia chemical potential equivalent to almost 80 mV and, simultaneously, an increase in proton electrochemical potential (⌬p) of about 24 mV with resultant de novo synthesis of ATP (428).…”
Section: Energy-yielding Pathwaysmentioning
confidence: 85%
“…Experimental support for the generation of a transmembrane potential, with resultant ATP synthesis through the ureaplasmal F O F 1 -type ATPase, first provided by Romano et al (383) was more recently extended and confirmed by Smith et al (428). At an external pH of 6.0, the pH optimum for ureaplasma growth in vitro, urea hydrolysis generated an ammonia chemical potential equivalent to almost 80 mV and, simultaneously, an increase in proton electrochemical potential (⌬p) of about 24 mV with resultant de novo synthesis of ATP (428). When the external pH of the growth medium reaches about 8.1, due to ammonia released from the cells, the intracellular pH rises to 8.6 and urease activity ceases (as shown by the pH activity profile of the ureaplasmal urease).…”
Section: Energy-yielding Pathwaysmentioning
confidence: 85%
See 3 more Smart Citations